Amino acid metabolism reprogramming in response to changing growth environment in Ginkgo biloba leaves. (June 2021) - Guo, Ying; Wang, Mengke; Gao, Caiyun; Fu, Fang-Fang; Wang, Tongli; El-Kassaby, Yousry A.; Wang, Guibin
Abstract: Widely distributed in Ginkgo leaves, the amino acids play an important role in the tree growth and Ginkgo products quality determination. Nevertheless, the biosynthesis and accumulation of amino acids have not been fully studied, especially in response to complex environmental conditions. Here, we integrated and analyzed transcriptome and metabolome from Ginkgo leaves originated from clonal homogeneous materials including their different genders (female and male) grown in three different habitats to reveal the environmental response mechanism of amino acid metabolism. Principal component analysis revealed the environmental dependence of amino acid accumulation in Ginkgo leaves, that is, the content of amino acids differed significantly between samples from different environments, while it was similar between female and male samples grown in the same environment. Weighted gene correlation network analysis suggested that the overexpression of structural genes in phenylpropanoid biosynthesis pathway and genes encoding receptor-like kinases, which was regulated by multiple transcription factors, were closely related to the amino acids' accumulation. Further, we indicated that environmental conditions directly affected the C and N flow allocation in leaves, thereby having an impact on the yield and quality (carbohydrates and amino acids contents) of Ginkgo tea. Highlights: Amino acids accumulation in Ginkgo leaves is environment-dependent. Receptor-like kinase genes are involved in the regulation of amino acid synthesis. Environmental condition directly affected C and N flow allocation.